Energy optimization for the process industries - Zhu, Frank Xin X. (John Wiley and Sons, Inc., 2014)
"This book centers around four kinds of energy improvement opportunities. The first is in operation improvement opportunities which occur due to operation variability and variations in feeds and products. This usually involves establishing the best operation practices and optimizing set points for control systems. The second comes from improved heat recovery within and across process units, which requires design changes to process flow schemes and heat exchange schemes. The third one is the use of state-of-the-art process and equipment technology for enhanced processing efficiency. The final one comes from better operation and planning of utility system. In this book, these topics are discussed and the methods for opportunity identification, assessment and implementation are introduced.The book provides methods and techniques for analysis, optimization, engineering design, and monitoring, which are required to identify, assess, implement and sustain energy improvement opportunities. The analysis methods are used for energy benchmarking and gap assessment while optimization methods are used for operation improvement, heat integration and utility system optimization. Engineering methods are applied for developing energy revamp projects while monitoring methods are used for establishing energy management systems.Topics Include: Benchmarking, Methods for Identifying Improvement Ideas, Total Site Energy Optimization, and Energy Optimization for Revamp Process Design"--